A prospective randomized comparison between pylorus‐ and subtotal stomach‐preserving pancreatoduodenectomy on postoperative delayed gastric emptying occurrence and long‐term nutritional status. Issue 7 (12th March 2014) - Matsumoto, Ippei; Shinzeki, Makoto; Asari, Sadaki; Goto, Tadahiro; Shirakawa, Sachiyo; Ajiki, Tetsuo; Fukumoto, Takumi; Suzuki, Yasuyuki; Ku, Yonson
<x xml:space="preserve">Abstract</x> Background and Objectives Pylorus‐preserving pancreatoduodenectomy (PPPD) has been associated with a high incidence of delayed gastric emptying (DGE). There are few studies comparing DGE associated with PPPD and subtotal stomach‐preserving pancreatoduodenectomy (SSPPD). Moreover, differences between the procedures with respect to long‐term results have not been reported. A prospective randomized study was conducted to compare perioperative complications and long‐term nutritional status with PPPD and SSPPD. Methods One hundred patients with periampullary lesions were randomized to receive either PPPD (n = 50) or SSPPD (n = 50). All patients were followed up for 3 years after surgery or to the time of recurrence to evaluate nutritional status for the study. The effects of the procedure, age, and malignancy on changes in nutritional indicators were estimated with linear mixed models. This study was registered at UMIN Clinical Trials Registry (UMIN 000012337). Results The incidence of DGE assessed by the International Study Group of Pancreatic Surgery was 20% with PPPD and 12% with SSPPD (P = 0.414). There were no significant differences between the two procedures on postoperative serum albumin levels, serum total cholesterol levels, and body mass index during the 3‐year follow‐up period. Conclusions SSPPD is equally effective in DGE occurrence rate and long‐term nutritional status comparing to PPPD. J. Surg. Oncol 2014; 109:690–696. © 2014 Wiley Periodicals, Inc.